Ammonothermal Synthesis and Crystal Growth of the Chain‐type Oxonitridosilicate Ca1+xY1–xSiN3–xOx (x > 0). Issue 18 (16th April 2020) - Mallmann, Mathias; Maak, Christian; Schnick, Wolfgang
Abstract : The oxonitridosilicate Ca1+ x Y1– x SiN3– x O x ( x > 0) was synthesized in custom‐built high‐temperature autoclaves starting from CaH2, intermetallic YSi and NaN3 using supercritical ammonia as solvent at a maximum pressure of 140 MPa and temperature of 1070 K. In situ formed NaNH2 acts as ammonobasic mineralizer and increases the solubility of the other starting materials. Air and moisture sensitive rod‐shaped single crystals of the title compound with length of up to 200 μm were obtained. The crystal structure was solved and refined by single‐crystal X‐ray diffraction. The results are supported by powder X‐ray diffraction, energy dispersive X‐ray spectroscopy and lattice energy (MAPLE) calculations. Ca1+ x Y1– x SiN3– x O x ( x > 0) is isostructural to Ca2 PN3 and Eu2 SiN3 and crystallizes in the orthorhombic space group Cmce (no. 64) with a = 5.331(2), b = 10.341(4), c = 11.248(4) Å and Z = 8 ( R 1 = 0.0257, wR 2 = 0.0447) and contains infinite zweier single chains running along [100] which are built up from corner sharing Si(N, O)4 tetrahedra. Abstract :